Ecuador : First Review under the Extended Fund Facility Arrangement, Requests for Waiver of Nonobservance of Performance Criterion, Modification of Performance Criteria, and Financing Assurances Review-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
A 36-month EFF with access of SDR 3.035 billion (435 percent of quota or about USD 4.204 billion) was approved on March 11, 2019. Economic activity is projected to decelerate further in 2019 as fiscal consolidation and a slowdown in credit growth weigh on economic growth. However, external financing conditions have improved on the back of rising oil prices and the approval of the IMF program, with sovereign bond spreads falling by 250 basis points since January 1, 2019.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; Sovereign Debt